The historical review of tick-borne encephalitis study in Tomsk - M. R. Karpova; N. G. Zhoukova; N. I. Komandenko (Бюллетень сибирской медицины)
The review of principal stages of tick-borne encephalitis study in Tomsk is presented in the article.